Activation of a fibroblast-specific enhancer of the proalpha2(I) collagen gene in tight-skin mice. - Denton, C; Zheng, B; Shiwen, X; Zhang, Z; Bou-Gharios, G; Eberspaecher, H; Black, C; de Crombrugghe, B (2001)
OBJECTIVE: Reporter transgenes were introduced into the type 1 tight-skin (Tsk1/+) mouse model of scleroderma to test the hypothesis that fibroblast-specific genetic programs are activated in fibrosis. METHODS: Transgenes harboring upstream fragments of the 5' flanking region of the mouse proalpha2(I) collagen gene (Col1a2), linked to a 400-bp minimal Col1a2 promoter driving an Escherichia coli beta-galactosidase (LacZ) reporter gene, were introduced into Tsk1/+ mice by breeding. Expression of these transgenes, which function as lineage-specific markers of fibroblast differentiation, was compared between the Tsk-LacZ mice and non-Tsk littermates. Responsiveness of these constructs to the profibrotic cytokine, transforming growth factor beta1 (TGFbeta1), was investigated by transient transfection of reporter constructs in tissue-culture cells. RESULTS: There was significant activation of reporter genes harboring the upstream enhancer in Tsk1/+ mice starting from 1 week of age. This was maximal at 6 weeks old (mean +/- SD 237 +/- 24% of non-Tsk controls; P= 0.001). Recombinant TGFbeta1 significantly activated reporter genes regulated by the upstream enhancer in transient transfection, and Tsk-LacZ fibroblasts showed elevated LacZ expression in tissue culture. CONCLUSION: These data suggest that activating signals in Tsk1/+ mice may act via fibroblast-specific regulatory elements within the murine Col1a2 gene. Although TGFbeta has been implicated in the pathogenesis of fibrosis, and reporter genes regulated by the upstream enhancer appear to be TGFbeta responsive in vitro, our results suggest that fibroblast-specific pathways may also be involved.